Factors on drug addiction: a case study at the cure & care rehabilitation centre (CRCC) / Badariah Mohd Saad ... [et al.] - Mohd Saad, Badariah; Soo, Cheng Chuah; Baharudin, Azfar Hilmi; Mohamad Khan, Noor Rita (UiTM Cawangan Johor, 2019)
This study was carried out using purposive sampling method. A total of 180 questionnaires were distributed to one of the Cure & Care Rehabilitation Centre (CCRC) in the state of Kedah and only 151 are usable. Self-administrated questionnaire that comprised two parts of questions was applied. All of the respondents are male with majority of them are Malay (96.70%). One hundred thirty-seven (90.73%) of the respondents had secondary education level. The 17 items of questions on 151 respondents were analyzed using principal component analysis (PCA) with a Varimax (orthogonal) rotation. PCA revealed the presence of four components with eigenvalues more than 1. The identified four components are measures of religion, law awareness, peer influence and lifestyle. Multiple regression analysis was carried out to investigate the effects of explanatory factors of religion, law awareness, peer influence and lifestyle on drug addict. The model of this study is fit as the model is significant with F-value of 14.527 (p < 0.01). The R2 value 0.286 indicates that the 28.6% of variations in drug addict is explained by the explanatory factors chosen in this study. Results shows that law awareness (b = 0.408, p < 0.05, BCa 95% CI 0.230, 0.290]), peer influences (b = 0.268, p < 0.05, BCa 95% CI [0.146, 0.414], and lifestyle (b = 0.096, p < 0.05, BCa 95% CI [0.014, 0.174]) have significant and positive effect on drug addict. While, religion was having no significant effect on drug addict.